Evaluation of the Effectiveness of Civil Servant Recruitment Based on Regulation Changes in Indonesia - Ibrahim Kristofol Kendi (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
This research explores changes in personnel regulations that reflect the government's efforts to consistently boost the human resource capacity of state apparatus. Law No. 8/1974 emphasizes ideological loyalty and administrative requirements without a competency-based system. Law No. 43 of 1999 introduced the principle of merit and competency-based selection, although it is still constrained by supervision and technology. Significant reforms occurred in the State Civil Service Law with the implementation of comprehensive meritocratic principles using technology such as Computers Assisted Test (CAT), and supervision by independent institutions such as KASN and BKN. The results of the study indicate an increase in effectiveness in transparency, accountability, and professionalism of civil servants along with the development of regulations, although implementation challenges in the regions remain obstacles. This study recommends strengthening technological infrastructure, supervision, and ASN training to support sustainable bureaucratic reform.